Agricultural machinery - from local forge or foreign factory? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
African blacksmiths and engineers are manufacturing agricultural machinery and are helping to decrease reliance on imports. However many obstacles still stand in the way of the successful development of their businesses. For many years most of the...